1998
DOI: 10.1101/gad.12.5.734
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control of chorion gene amplification

Abstract: Over-replication of two clusters of chorion genes in Drosophila ovarian follicle cells is essential for rapid eggshell biosynthesis. The relationship of this amplification to the follicle cell cycles has remained unclear. To investigate the regulation of amplification, we developed a technique to detect amplifying chorion genes in individual follicle cells using BrdU incorporation and FISH. Amplification occurs in two developmental phases. One of the gene clusters begins to amplify periodically during S phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
336
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(364 citation statements)
references
References 64 publications
24
336
3
1
Order By: Relevance
“…The proteolysis of Dup/Cdt1 is now known to be important to prevent rereplication during mitotic cycles of a variety of organisms (Arias and Walter 2007). The proposed importance of Dup regulation for endocycle licensing control is consistent with the observation that MCM proteins periodically associate with chromatin during the Gap phase of each endocycle, and measurements of DNA copy number that showed that most of the genome does not duplicate more than once per endocycle S phase (Lilly and Spradling 1996;Calvi et al 1998;Su and O'Farrell 1998;A. Kolpakas, S. Maqbool, and B. Calvi, unpubl.).…”
Section: Rereplication Is Distinct From the Normal Process Of Endoredsupporting
confidence: 61%
See 3 more Smart Citations
“…The proteolysis of Dup/Cdt1 is now known to be important to prevent rereplication during mitotic cycles of a variety of organisms (Arias and Walter 2007). The proposed importance of Dup regulation for endocycle licensing control is consistent with the observation that MCM proteins periodically associate with chromatin during the Gap phase of each endocycle, and measurements of DNA copy number that showed that most of the genome does not duplicate more than once per endocycle S phase (Lilly and Spradling 1996;Calvi et al 1998;Su and O'Farrell 1998;A. Kolpakas, S. Maqbool, and B. Calvi, unpubl.).…”
Section: Rereplication Is Distinct From the Normal Process Of Endoredsupporting
confidence: 61%
“…Egg chambers then move down a structure called the "ovariole" as they mature through stages of oogenesis (stages 1-14) (Spradling 1993). Follicle cells proliferate by a mitotic division cycle up to stage 6, and then switch to the endocycle by stage 7, undergoing three rounds of G/S endoreduplication by stage 10A (Mahowald et al 1979;Lilly and Spradling 1996;Calvi et al 1998;Deng et al 2001;Lopez-Schier and St Johnston 2001). Thereafter, they selectively rereplicate only a few loci, resulting in amplification of gene copy number (Calvi et al 1998).…”
Section: Elevated Dup Protein Induces Rereplication In Mitotic Cyclinmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional conserved DNA replication factor genes required for chorion gene amplification include those encoding Cyclin E (Calvi et al, 1998), E2F (Royzman et al, 1999), DP (Royzman et al, 1999), RBF (Bosco et al, 2001), CDT1 (Whittaker et al, 2000), geminin (Quinn et al, 2001) and MCM6 (Schwed et al, 2002). Antibody to ORC1 or ORC2 reveals that, coincident with the initiation of amplification, ORC moves from a diffuse nuclear distribution into dramatic foci localized at the chorion gene loci (Asano and Wharton, 1999;Calvi et al, 1998;Royzman et al, 1999). The data demonstrate that Drosophila chorion gene amplification uses evolutionarily conserved machinery for initiation; however, some mechanism must exist to uniquely mark the chorion gene loci origins for activation during amplification, when overall genomic replication has ceased.…”
Section: Introductionmentioning
confidence: 99%